Bank-firm equity-based relationships and firm's performance: Evidence from Islamic and conventional banks of OIC countries - Shahbaz Khan; Nida Baig; Shahzad Hussain; Muhammad Usman; Humera Manzoor (Cogent Business & Management, 2021)
We examine the relationship between bank's equity ownership and corporate financial performance based on cross-sectional data through 2SLS estimation model. Our evidence is based on listed 3203 non-financial firms of 16 Organization of Islamic Conference (OIC) member states with dual-banking system (Islamic and Conventional). Consistent with notion of previous empirical studies, we document a positive impact of both Islamic and Conventional bank-firm equity-based relationships on firm's performance. The study suggests that the presence of bank equity ownership mitigates agency cost and information asymmetry problems, which in turn increase the firm's performance. Hence, the market participants such as portfolio managers may consider the role of financial intermediaries during the construction of risk minimization strategies.
Keywords: G24; G32; L25; 650; Bank-Firm Equity-Based Relationships; Islamic Banks’ Equity Shareholdings; Conventional Banks’ Equity Shareholdings; Firm’ s Performance; OIC